Assessment of axillary lymph nodes involvement in patients with breast cancer depending on the tumor size and its histological and nuclear grades - Bojić Toplica; Đorđević Nebojša; Karanikolić Aleksandar; Filipović Slađana; Granić Miroslav; Poultsidi Antigoni A. (Vojnosanitetski Pregled)
Background/Aim. There are a lot of studies aiding to the opinion that the involvement degree of axilla lymph nodes grows depending on increase of breast tumor size, and its histological and nuclear grades. The aim of this study was to assess the risk of axillary lymph nodes involvement, as well as the relation between the tumor size, histological and nuclear grades in a group of female patients who underwent breast cancer surgery, including levels 1-3 axillary dissection. Methods. Investigation covered 900 patients operated on during 2005-2008 who underwent modified radical mastectomy including axillar dissection. We assessed a number of involved lymph nodes, depending on tumor macroscopic size (T), histological grade (HG) and nuclear grade (NG). Results. A total number of examined lymph nodes was 9977. The incidence of involved lymph nodes was from 18.6% with T1 tumor size up to 60.2% with T4 tumor size. Concerning histological grade, the number of involved lymph nodes ranged from 14.2% (HGI) to 45.1% (HGIII); while in terms of nuclear grade, the number of involved lymph nodes ranged from 17.4% (NGI) to 54.5% (NGIV). By using χ2-test for trend and odds ratio (OR), the results showed that the axillary lymph nodes involvement degree was increased with the increase of the tumor size and its histological and nuclear grades. The risk of axillary lymphatic nodes involvement was 1.43 times higher in the group of T2 tumors size compared to the smaller tumors T1 size, and even up to 6.62 times higher in case of T4 tumor size. It was also increasied from 1.79 times for HGII to even 4.98 times for HGIII, and from 1.44 times for NGII to 5.71 times for NGIV. Conclusion. In breast cancer patients, there is a strong correlation between tumor size, its histological and nuclear grades and the risk of axillary lymph nodes involvement.